Rights of Police Action by the Financial Audit Board of the Republic of Indonesia - Bintari, Aninditya Eka (Universitas Negeri Semarang, 2017)
This study aims to describe the actions of the police conducted by the Financial Audit Board of the Republic of Indonesia (BPK RI) in the perspective of human rights in the context of the ethics code and the fulfillment of rights. This research is normative law research, hence secondary data source or library data source used as the main source of this research. The research method used in this research is qualitative analysis, which is descriptive by presenting the data in detail and make interpretations to answer the formulation of research problems. The conclusion of the research result is police action stipulated in Article 24 of Law No. 15 of 2006 on Indonesian Financial Audit Board which contains the police action conducted by BPK to examine a case conducted by order of the Attorney General after first obtaining written approval from the President. What is meant by police action (explanation of Article 24 of Law No. 15 of 2006) is a summons in connection with criminal acts, arrest, search and seizure. This police action is further regulated in BPK RI Regulation No. 2 of 2008 concerning to the Procedure of Sealing in Implementation of Inspection and Regulation of BPK RI No.3 of 2008 concerning Procedure of Calling and Request of Information by BPK.